FEASIBILITY OF COOPERATION AMONG STAKEHOLDERS IN CAR SHARING BUSINESS IN METROPOLITAN AREAS OF JAPAN - KUSUMOTO, Jun; SUZUKI, Satoshi; KATO, Hironori; KAYAMA, Shinsuke; KAWANOBE, Takeshi (SOCIOTECHNICA, 2011)
This paper examines the feasibility of cooperation among stakeholders in car sharing business in Japan. First, we interview ten stakeholders regarding the car sharing business, including the car sharing operators, rail operators, bus operators, local governments and central government. We abstract the stakeholders' recognitions of problem structure of car sharing through interviewing them. Then, we analyze the feasibility of cooperation among stakeholders. The results show that the joint business of car sharing with public transit service could be realized if the public transit operators find the benefit from the car sharing business.